2013
DOI: 10.1111/ijpp.12067
|View full text |Cite
|
Sign up to set email alerts
|

Australian caregivers’ management of childhood ailments

Abstract: The ability of caregivers to accurately measure and administer doses is important. Determining the motivations to use medicines, as well as dosing behaviours is necessary to improve the quality use of medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…As fever is a symptom that all children will suffer and all caregivers will need to manage, it is promising that weight-based as opposed to age-based dosing was seen in a large proportion of the encounters in this study. However, this weight-based dosing advice contrasts with parents actual actions seen in a previous study 14 so understanding how a caregiver interprets dosing information is important research to pursue. It should also be noted that many children with fever do not require antipyretic treatment and that over treatment of fever due to fever phobia and misconceptions is not just a caregiver issue but many health professionals also lack appropriate knowledge.…”
Section: R a F T A J P E A C C E P T E D D R A F Tmentioning
confidence: 90%
“…As fever is a symptom that all children will suffer and all caregivers will need to manage, it is promising that weight-based as opposed to age-based dosing was seen in a large proportion of the encounters in this study. However, this weight-based dosing advice contrasts with parents actual actions seen in a previous study 14 so understanding how a caregiver interprets dosing information is important research to pursue. It should also be noted that many children with fever do not require antipyretic treatment and that over treatment of fever due to fever phobia and misconceptions is not just a caregiver issue but many health professionals also lack appropriate knowledge.…”
Section: R a F T A J P E A C C E P T E D D R A F Tmentioning
confidence: 90%
“…These higher order outcomes need their measurement tool to be constructively aligned to guarantee that the skills taught have a long‐lasting effect and consolidation. Recent articles by Hietbrink () and Emmerton () observed that the proportions of parent with skills to dose their child accurately on weight were between 30%–33%, highlighting that parents continue to inappropriately handle medication dosing for children with fever. Therefore, it is imperative that future educational interventions targeting medication dosing skills should be aimed to assess and improve outcomes at higher levels of Miller's pyramid and should be evaluated through observation, rather than through self‐reported survey.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have also highlighted that education should focus on skills development-the higher levels of Millar's competency pyramid (Miller, 1990) as the "Knows" and "Knows how" region are mainly intermediary markers and not true reflections of lasting change in practice. In particular, the functional health literacy of caregivers and their accuracy in measuring doses have been shown to be exceptionally poor (Emmerton et al, 2014;Hietbrink, Bakshi, & Moles, 2014;Parker & Gazmararian, 2003 Many of the studies in fact did not seem to have an assessment measure constructively aligned (Biggs, 2003) with the educational intervention objectives. For example, the study by Huang [S21]…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that 20% of the parents did not administer medication at the correct intervals (Hietbrink et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…, Tzimenatos & Bond , Mehndiratta , Hietbrink et al . ). Neuspiel and Taylor () reviewed 78 studies on medication errors made by caregivers of children.…”
Section: Introductionmentioning
confidence: 97%